Implementation of Project Based Learning (PjBL) Learning Model with Canva Application to Increase Students' Interest in Learning Atomic Structure Material in Class X - Dame Putri Samosir; Hendra Simanjuntak; Hisar Marulitua Manurung (STABN RADEN WIJAYA WONOGIRI, 2021)
This research aims to determine the application of the Project Based Learning (Pjbl) Learning Model with the Canva Application to Increase Students' Interest in Learning in Atomic Structure Material in Class X. The type of research that will be used in this research is quantitative research with experimental methods. The form of research used in this research is true experimental design. This research was conducted at Nommensen Pematangsiantar Private High School located at Jl. Sangnawaluh, No.4, Siopat Suhu, Kec. Siantar Tim., Pematang Siantar City, North Sumatra 21136. Based on the research results obtained, it can be concluded that: There is an influence of the Project Based Learning learning model with Canva to increase students' interest in learning the material. atomic structure in class . This proves that the experimental class has better interest in learning compared to the control class Keywords: Learning Model, Project Based Learning (Pjbl), Canva Application, Interest in Learning